The Influence of Price and Product Quality on Home Purchasing Decisions - Gayatri, Ni Putu Krishna Ananda Satya; Nayotama, A A Endra Danasura (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
This study examines the influence of price and product quality on home purchasing decisions. The population includes individuals or families planning to buy a house or who have purchased one in the last five years. Using purposive sampling, 36 respondents were selected based on the Slovin formula with a 5% margin of error. Data were gathered through a questionnaire employing a five-point Likert scale. Regression analysis revealed that price has a positive and significant effect on purchasing decisions (t = 13.936; p = 0.000), aligning with consumer behavior theory, which highlights price as a key factor—especially in the property sector. Similarly, product quality significantly affects home buying decisions (t = 3.021; p = 0.005), emphasizing the importance of elements such as materials, design, and facilities. The coefficient of determination (R² = 0.876) indicates that 87.6% of the variation in home purchasing decisions is explained by price and product quality, while the adjusted R² (0.868) confirms strong model reliability. These findings suggest that property developers should prioritize competitive pricing and quality improvements to align with consumer preferences and enhance market competitiveness.